THE VULNERABILITY OF NETWORKED USERS (TEST BioLaw Journal - Rivista di BioDiritto, 2024)
The digital platforms express particularly pervasive forms of manifestation of economic and social power. The platform economy exploits users’ passions and penetrates the most vulnerable recesses of people. The European Union has launched a strategy aimed at regulating the most problematic aspects of the relationship between users and platforms, which to date have been embodied in a digital regulatory package. The regulatory acts are concerned with protecting – with some criticality – the vulnerable categories that interface with the network.
Keywords: digital platforms; digital constitutionalism; artificial intelligence; State; vulnerability